2019
DOI: 10.1111/tid.13130
|View full text |Cite
|
Sign up to set email alerts
|

When medicine transforms art

Abstract: A 40-year-old female from Canada with a history of type 1 diabetes mellitus, diabetic retinopathy, and solitary pancreas transplant, presented with increase in her pancreatic enzymes 1-year post-transplant. Her induction immunosuppression consisted of anti-thymocyte globulin and maintenance immunosuppression at the time of her presentation was cyclosporine, mycophenolate mofetil and low-dose prednisone. Other medical history was significant for failed islet cell transplant in 2003 and prolonged neutropenia tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…One recent study demonstrated that voriconazole may be more effective than itraconazole [124]. However, voriconazole carries the risk of significant adverse effects, including neurotoxicity, phototoxicity, increased risk of dermatologic malignancies, and periostitis [125][126][127]. The phenomenon of accelerated metabolism (also referred to as autoinduction) that is particular to voriconazole requires attention and regular therapeutic drug monitoring [128].…”
Section: Triazolesmentioning
confidence: 99%
“…One recent study demonstrated that voriconazole may be more effective than itraconazole [124]. However, voriconazole carries the risk of significant adverse effects, including neurotoxicity, phototoxicity, increased risk of dermatologic malignancies, and periostitis [125][126][127]. The phenomenon of accelerated metabolism (also referred to as autoinduction) that is particular to voriconazole requires attention and regular therapeutic drug monitoring [128].…”
Section: Triazolesmentioning
confidence: 99%